Emergent Bilingualism and Working Memory Development in School Aged Children. (September 2016) - Hansen, Laura Birke; Macizo, Pedro; Duñabeitia, Jon Andoni; Saldaña, David; Carreiras, Manuel; Fuentes, Luis J.; Bajo, M. Teresa
Abstract : The present research explores working memory (WM) development in monolingual as well as emergent bilingual children immersed in an L2 at school. Evidence from recent years suggests that bilingualism may boost domain‐general executive control, but impair nonexecutive linguistic processing. Both are relevant for verbal WM, but different paradigms currently in use vary in the degree to which they reflect these subprocesses. We found that only younger immersion students outperformed monolinguals on the n‐back task, a measure of executive WM updating, but showed a relative deficit in L1 rapid naming and, to a lesser degree, reading span scores. Age effects suggest that, rather than ultimate performance levels, bilingualism alters the developmental course of WM processes. We conclude that emergent bilingualism may modulate WM development in school‐aged children at the subcomponent level, but detecting this modulation is contingent on task selection.